Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $E \simeq M \times \mathbb C$ be a trivial smooth complex line bundle over the Riemann surface $M$ and let $S \colon M \to E$ be its smooth nowhere vanishing section. Let $\nabla^1$ and $\nabla^2$ be two covariant derivatives on $E$, then $$ \nabla^1 S=S \otimes X^1,\\ \nabla^2 S = S \otimes X^2, $$ where $X^1$, $X^2 \in \Omega^1(M)$ are called the connections' one-forms. It is stated that if $dX^1 = dX^2$ then curvatures of $\nabla^1$ and $\nabla^2$ are the same. I tried to show this by definition but I have a problem. Let $U$, $V \in \Gamma(TM)$, $f \in C^\infty(M)$. Then $$ \nabla^1_U \nabla^1_V (fS) = \nabla^1_U ( (V(f)+fX^1(V))S) \\ = \bigl( U(V(f))+U(f)X^1(V)+fU(X^1(V)) + X^1(U)(V(f)+fX^1(V)) \bigr)S $$ and hence $$ \nabla^1_U \nabla^1_V(fS)-\nabla^1_V \nabla^1_U(fS) \\ = \bigl([U,V](f)+fU(X^1(V))-fV(X^1(U)) \bigr)S, $$ and then $$ R^1(U,V)(fS) = \nabla^1_U \nabla^1_V(fS)-\nabla^1_V\nabla^1_U(fS)-\nabla^1_{[U,V]}(fS) \\ = \bigl( U(X^1(V))-V(X^1(U))- X^1([U,V])\bigr)fS $$ But how to show that this expression depends only on $dX^1$?

share|cite|improve this question
up vote 3 down vote accepted

There is the following formula for the exterior derivative that you should get to know (it comes up a lot):

In the case of a 1-form $\mu$, it says that $$ d\mu(U,V) = U\cdot \mu(V) - V \cdot \mu(U) - \mu([U,V]). $$ Therefore the last thing you wrote is exactly $dX^1(U,V)$.

This formula can be proved using Cartan's formula: $$ d i_U \mu + i_U d \mu = L_U \mu. $$ Rearranging gives $$ i_U d\mu = L_U \mu - d(\mu(U)). $$ Now apply to a vector field $V$ and get $$ d\mu(U,V) = (L_U \mu)(V) - V\cdot \mu(U). $$ Now we use the fact that the Lie derivative satisfies the product rule: $$ U\cdot (\mu(V)) = L_U (\mu(V)) = (L_U \mu)(V) + \mu(L_U V) = (L_U \mu)(V) + \mu([U,V]). $$ So $(L_U \mu)(V) = U\cdot(\mu(V)) - \mu([U,V])$, as desired.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.